Crossing Eurasia: trans-regional Afghan trading networks in China and beyond. Issue 1 (2nd January 2016) - Marsden, Magnus
Abstract : An expanding body of literature in the field of Central Asian studies has brought attention to the problems of considering the region's complex dynamics through the lens of its nation-states. Comparatively less attention has been paid to the role played by trans-regional circulations in connecting parts of Central Asia to the wider world. This paper situates ethnographic work on trans-regional networks of Afghan traders in China, Central Asia, Russia, Ukraine and the UK in relation to the literature on trans-regional connections and circulation societies. Ethnographically it demonstrates the multi-polar nature of these trans-regional networks, and the importance of trading nodes, especially the Chinese city of Yiwu, to their formation and ongoing vitality.